ANCAMAN MAFIA PERADILAN TERHADAP EKSISTENSI NEGARA HUKUM - Hamdan Zoelva (VERITAS, 2017)
Law enforcement of judicial mafia lies in the quality of its institutions, or on thelegal structure dimension. The quality of this institution is closely related to thequality and integrity of the apparatus within it, the integrity of the apparatus mustbe ensured since the recruitment process and maintained and maintained in thecoaching process. Judicial mafia arises because of the collusion among theelements of the stakeholders of the judiciary, the destruction of the stakeholdersthat led to the emergence of various judicial mafia practices in Indonesia. Thecourt as the last bastion of justice and law enforcement is certainly expected to beindependent and impartial in accordance with the demands of the rule of law. Thecourt institution can not be independent and impartial if there is still a network ofcrimes that undermine our judicial system. Courts that only give justice to thosewho are strong and have access, will cultivate what is feared by Tamahana thatlaw is only a tool (law as instrumentalism) for those who have access and power.This is where the threat to the principle of Indonesian legal state.